Protective Immunity Induced by TgMIC5 and TgMIC16 DNA Vaccines Against Toxoplasmosis - Zhu, Yu-Chao; Ma, Li-Juan; Zhang, Ji-Li; Liu, Jian-Fa; He, Yong; Feng, Ji-Ye; Chen, Jia (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasma gondii is an obligate intracellular parasite, which is responsible for a widely distributed zoonosis. Effective vaccines against toxoplasmosis are necessary to protect the public health. The aim of this study is to evaluate the immune efficacy of DNA vaccines encoding TgMIC5 and TgMIC16 genes against T. gondii infection. The recombinant plasmid pVAX-MIC5 and pVAX-MIC16 were constructed and injected intramuscularly in mice. The specific immune responses and protection against challenge with T. gondii RH tachyzoites were evaluated by measuring the cytokine levels, serum antibody concentrations, lymphocyte proliferation, lymphocyte populations, and the survival time. The protection against challenge with the T. gondii RH tchyzoites and PRU cysts was examined by evaluation of the reduction in the brain cyst burden. The results indicated that immunized mice showed significantly increased levels of IgG, IFN-γ, IL-2, IL-12p70, and IL-12p40 and percentages of CD4+ and CD8+ T cells. Additionally, vaccination prolonged the mouse survival time and reduced brain cysts compared with controls. Mouse groups immunized with a two-gene cocktail of pVAX-MIC5 + pVAX-MIC16 were more protected than mouse groups immunized with a single gene of pVAX-MIC5 or pVAX-MIC16. These results demonstrate that TgMIC5 and TgMIC16 induce effective immunity against toxoplasmosis and may serve as a good vaccine candidate against T. gondii infection.